Penyuluhan Kesehatan : Edukasi Gizi Seimbang pada Remaja Putri di SMP Negeri 2 Bunta, Kabupaten Banggai, Provinsi Sulawesi Tengah - Mariyati Mariyati; Zamli, Zamli (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The number of school-age adolescent girls in Banggai Regency, Central Sulawesi, still faces serious challenges related to nutritional problems such as anemia and chronic energy deficiency (SEZ). Low nutritional literacy and unbalanced food consumption habits also worsen their nutritional status, especially during puberty when nutritional needs increase significantly. This service activity aims to increase the understanding and awareness of young women on the principles of balanced nutrition through a participatory educational approach. The implementation of the activity was carried out at SMP Negeri 2 Bunta, Simpang Raya District, involving 30 students in grades VII and VIII as well as UKS supervisory teachers. The intervention included providing material on "Fill My Plate", the 4 pillars of balanced nutrition, and the risk of nutritional disorders in adolescents. The material was delivered in the form of interactive counseling using leaflet media, accompanied by knowledge measurement through pre-test, post-test, and one-week post-activity evaluation. The results of the activity showed a significant increase in students' understanding of the principles of balanced nutrition, with the knowledge score of the good category increasing from 40% to 87%. Most of the participants were able to mention the composition of the meal portion, the importance of breakfast, restrictions on fast food consumption, and the need to drink enough water every day. This activity also has an impact on increasing the capacity of teachers in assisting and monitoring the health status of students through the UKS program. Teachers become more active in conducting periodic counseling and recording the nutritional development of female students on a regular basis. School-based balanced nutrition counseling has been proven to be effective in improving adolescent nutritional literacy. This educational model can be replicated in other regions with cross-sectoral support such as education offices, health centers, and village governments, to support the achievement of sustainable development goals in the health sector.